2022
DOI: 10.3390/molecules27238296
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Understanding of Two-Pore Domain TASK Potassium Channels and Their Potential as Therapeutic Targets

Abstract: TWIK-related acid-sensitive K+ (TASK) channels, including TASK-1, TASK-3, and TASK-5, are important members of the two-pore domain potassium (K2P) channel family. TASK-5 is not functionally expressed in the recombinant system. TASK channels are very sensitive to changes in extracellular pH and are active during all membrane potential periods. They are similar to other K2P channels in that they can create and use background-leaked potassium currents to stabilize resting membrane conductance and repolarize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…Isoflurane activates TASK-1/3 channels with subsequent neuroprotective effects ( Liu et al, 2005 ; Yao et al, 2017 ). TASK-1/3 potassium channels are strongly expressed in neurons throughout the CNS ( Talley et al, 2001 ; Fan et al, 2022 ) as well as in mitochondria ( Szewczyk et al, 2009 ). Numerous studies have found isoflurane to have neuroprotective and cardioprotective properties in various injury models through actions on TASK-1/3 and other potassium channels ( Liu et al, 2005 ; Park et al, 2005 ; Khatibi et al, 2011 ; Taheri et al, 2014 ; Altay et al, 2020 ; Zhai et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane activates TASK-1/3 channels with subsequent neuroprotective effects ( Liu et al, 2005 ; Yao et al, 2017 ). TASK-1/3 potassium channels are strongly expressed in neurons throughout the CNS ( Talley et al, 2001 ; Fan et al, 2022 ) as well as in mitochondria ( Szewczyk et al, 2009 ). Numerous studies have found isoflurane to have neuroprotective and cardioprotective properties in various injury models through actions on TASK-1/3 and other potassium channels ( Liu et al, 2005 ; Park et al, 2005 ; Khatibi et al, 2011 ; Taheri et al, 2014 ; Altay et al, 2020 ; Zhai et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protons released by Glu, GABA or ACh acidify the inter-synaptic space and can activate acid-sensitive receptors at the postsynaptic termination together with specific receptors for Glu, GABA and ACh. There are numerous proton-sensitive receptors in the postsynaptic termination [139], both ionotropic such as ASICs [39,117], TRPV1 [41,[140][141][142], CaV3 [143] and metabotropic, of the TASK type [144] and GPCRs [43]. The proton activation of the postsynaptic receptor can foster the opening of ionic channels [103,145], depolarization and the generation of a new action potential, enabling the impulse to continue [23,59,146].…”
Section: Synaptic Transmission Of the Impulsementioning
confidence: 99%
“…The protons released by Glu, GABA or ACh acidify the inter-synaptic space and can activate acid-sensitive receptors at the postsynaptic termination together with specific receptors for Glu, GABA and ACh. There are numerous proton-sensitive receptors in the postsynaptic termination, 138 both ionotropic such as ASICs, 39,116 TRPV1, 41,[139][140][141] CaV3 142 and metabotropic, of the TASK type 143 and GPCRs. 43 The proton activation of the postsynaptic receptor can foster the opening of ionic channels, 103,144 depolarization and the generation of a new action potential, enabling the impulse to continue.…”
Section: Synaptic Transmission Of the Impulsementioning
confidence: 99%